Post-conflict participatory arts : socially engaged development - Mkwananzi, Faith; Cin, Firdevs Melis (Abingdon, Oxon ; New York : Routledge, 2022)
"This book investigates the power of art to enhance human development and to initiate positive social change for individuals and societies recovering from conflict. Interventions aimed at reinforcing social justice and bringing communities together after conflict are often accused of being top-down, or failing to consider all groups and contexts within a society. The use of participatory arts can help to address these challenges by fostering community engagement, social cohesion, influencing public policy and ultimately, advancing social justice. Arts based methods can be particularly effective at reaching youth communities, providing voice and political agency to young people who are often not given a platform. Situated at the intersection of participatory arts, social and epistemic justice, this book brings together case studies from across the world to reflect on best practice for the use of bottom-up, participatory, co-produced and co-designed arts processes in conflict settings. This book provides an important guide to the role that arts can play in addressing epistemic injustice and contributing to social justice and human development. As such, it will be of interest to international development and arts practitioners, policy makers, and to students and researchers across participatory arts, youth studies, international development, social justice, and peace and conflict studies"--
Keywords: Arts and society; War and society; Art and social action; Artists and community; ART / Art & Politics